2023
DOI: 10.3390/foods12061348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano- and Microzinc Supplementation on the Mineral Composition of Bones of Rats with Induced Mammary Gland Cancer

Abstract: Background: The aim of this study was to determine changes in the mineral composition of the bones of rats with chemically induced mammary gland cancer and to attempt to establish whether a specific diet modification involving the inclusion of zinc ions in two forms—nano and micro—will affect the mineral composition of the bones. Methods: Female Sprague–Dawley rats were used for the research. The animals were randomly assigned to three experimental groups. All animals were fed a standard diet (Labofeed H), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…41,44 Numerous studies have consistently reported that ZnO nanocomposites exhibit selectivity towards cancer cells both in vitro and in vivo, demonstrating 28-35 times higher cytotoxicity compared to normal cells. 45 In an acidic environment, the concentration of Zn2+ has been found to play a significant role in related Treatment with nanocomposite materials resulted in increased expression of Bax and p53, decreased expression of Ki-67 and Bcl-2, reduction in cell size, and the appearance of cytoplasmic vacuoles and chromatin pyknosis. 47 Another study utilized ZnO NPs to encapsulate a complex of low molecular weight heparin (LMHP) and doxorubicin (DOX) (LMHP-DOX) to prepare ZnO LD NPs for controllable pH-triggered DOX release at the target site.…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…41,44 Numerous studies have consistently reported that ZnO nanocomposites exhibit selectivity towards cancer cells both in vitro and in vivo, demonstrating 28-35 times higher cytotoxicity compared to normal cells. 45 In an acidic environment, the concentration of Zn2+ has been found to play a significant role in related Treatment with nanocomposite materials resulted in increased expression of Bax and p53, decreased expression of Ki-67 and Bcl-2, reduction in cell size, and the appearance of cytoplasmic vacuoles and chromatin pyknosis. 47 Another study utilized ZnO NPs to encapsulate a complex of low molecular weight heparin (LMHP) and doxorubicin (DOX) (LMHP-DOX) to prepare ZnO LD NPs for controllable pH-triggered DOX release at the target site.…”
Section: Cancer Treatmentmentioning
confidence: 99%